Relative Importance of Emotional Intelligence’s Dimensions in Contributing to Dimensions of Job Performance - Jamil Ahmad; Maryam Saeed Hashmi (Journal of Basic & Applied Sciences, 2015)
Career in service industry is emotional labor intensive, which turns performance of the employees into undesired status who are not emotionally intelligent. To put light on this issue the present study scrutinizes the significant contributor from four dimensions of emotional intelligence to three dimensions of job performance individually as well jointly. Data gathered from 292 bankers through instrument adopted from literature, regression results revealed that self emotional appraisal, others emotional appraisal, regulation of emotions and use of emotions significantly contribute task performance, counterproductive work behaviors and organizational citizenship behaviors individually as well as jointly. The use of emotions remained significant when included with other dimensions of emotional intelligence in the hierarchical regressions model after controlling for age and gender, whereas regulation of emotions lost its significance. In organizational citizenship behaviors maximum variation was observed due to emotional intelligence’s dimensions as compare to the other dimensions of job performance. Banks’ management could use these findings for recruitment, training and promotions of employees. Limitations and future suggestions are presented in later part.